(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
As young children grow up with a continuous growth in their brain activity, they are better able to absorb new information faster than adults are with full brain activity. Given these characteristics, it is advisable to plan the lesson. For example, teaching children of pre-school age is often an effective way to use games, pictures, songs and poems and cartoons to teach a foreign language.